Schiff Base Complexes of lron(II) and Their Spectral Properties. - MEHTA , B.H.; V. PuRANDARE., KEDAR (Asian Journal of Chemistry, 2010)
A series of mononuclear Fe(II) complexes with a commercially important Schiff base has been synthesized. The mononuclear Fe(II) complexes have been obtained by the reaction of the ligand Schiff base which was derived from condensation of 2-hydroxy-1-naphthaldehyde with anthranilic acid, o-toluidine, p-toludine and aniline The recrystallised metal complexes were analysed for their elemental analysis and other analytical parameters. The structural diagnosis was inferred from various spectral measurements. The data was well supported by magnetic susceptibility measurements at room temperature.